KAJIAN MIKROBIOLOGI PADA PRODUK IKAN ASIN KERING YANG DIPASARKAN DI PASAR TRADISIONAL DAN PASAR SWALAYAN DALAM UPAYA PENINGKATAN KEAMANAN PANGAN DI KOTA JAMBI - Ridawati Marpaung (Universitas Batanghari Jambi, 2015)
The researchwas conducted in Jambi city to recognize the microbiology contamination rate of salted fish. There are seven kinds of salted fish that taken from each different kind of market e.g. tradisional market (Angso duo) and modern market (Hypermart). Plate Count Agar (TPA) method(SNI 01-2339-1991) was used to analyzed the number aerobic bacteria. The results showed that there was one kind among the seven kinds of salted fish that indicated as the higher contain of bacteria (7.30X104). This salted fish called was “Sepat” salted fish. Mine while the lowest amount of bacteria was contained in “KepalaBatu” salted fish (1,52X102). The important one should be noted that the bacteria contain in whole seven salt fishes was still save to be consumed, because the number of bacteria colony each salted fish in both kind of market was lower than the crisis level bacteria contamination (1X105).Keyword : microbiology, salted fish, bacteria colony, food safety